Determinants of Continuance Intention to Use Mobile Wallet Services : Light Users vs Heavy Users - Thirumal Reddy, T.; Madhusudhana Rao, B. (Indian Journal of Marketing, 2021)
Mobile technologies and rapid popularity & usage among the businesses and consumers have led to revolutionary changes in the way the goods and services are marketed and consumed. The impact of mobile based communication strategies among modern marketers are more commonly witnessed with the revolutionary growth of mobile applications and their usage. One of the significant developments of mobile technologies that prove to be beneficial to both businesses and customers is the introduction of mobile payment systems, otherwise known as mobile wallet applications. Despite many mobile wallet users in India, it is highly challenging for service providers to understand the motivations behind customers to be loyal because of divergent customer segments and their needs. Hence, this study aimed at identifying the factors that determine the mobile wallet users’ intentions to continue using a specific service provider and how this behaviour would be different across the customer groups based on their usage. This paper proposed a theoretical research framework and validated the same with empirical data with the help of multivariate data analysis techniques, including exploratory factor analysis, t-test, and MANOVA. Perceived usefulness, perceived ease of use, perceived enjoyment, and satisfaction were found to be the significant factors influencing users' intention to continue using mobile wallet applications. Finally, the results revealed that light users and heavy users differed significantly in terms of their overall post-adoption behaviour on mobile wallet applications.